Public Health Emergency of International Concern (PHEIC) has Declared Twice in 2014; Polio and Ebola at the Top - Mohammed A. Soghaier; Khwaja M.I. Saeed; Khushhal K. Zaman (AIMS Press, 2015)
Background: The current Ebola outbreak in West Africa and the large scale wild Polio virus outbreak in several countries are the top most issues among international public health and scientific communities' debates and concerns. These two outbreaks were judged to be declared as Public Health Emergency of International Concern (PHEIC) during 2014. This is the first time ever to have such circumstance of two PHEICs at the same time. Discussion: PHEIC, which has to be declared by WHO Director General after a recommendation of IHR Emergency Committee; is observed to start in countries with fragile health system and conflict areas. Then it rapidly spread to threaten the global public health. The year 2014 has uniquely witnessed declaration of two events as PHEIC according to IHR (2005); Polio and Ebola Virus Disease (EVD). Both outbreaks are caused by viruses such as H1N1 which was previously declared as PHEIC in 2009. Summary: Public Health Emergencies of International Concern in 2014 occurred in countries with weak health systems and conflicts and threatening the whole globe. International collaborative work is required to contain the event and to mobilize resources/capacities between countries. Moreover, public health surveillance systems as core capacity for IHR (2005) should be strengthened in all countries with focus on those with limited capacity and ongoing conflicts. The ultimate aim is timely detection of potential PHEIC events in the future along with early preparedness and response plans.